Managing risk factors for substance abuse among employees in the waste management sector: Perspectives from an Africa-based public waste management organization. (3rd July 2019) - Moloi, Esther Molebogeng; Geyer, Stephan
Abstract: The unique case of substance abuse among employees in the waste management sector seems inadequately described. Based on the perspectives of employees recently released from treatment centers for substance abuse, and their supervisors at a public waste management organization in South Africa, this study explored and described the risk factors for substance abuse in the waste management sector. As part of a collective case study, data were collected through semistructured interviews with employees ( n = 10) and a focus group discussion with supervisors ( n = 8). Recommendations are offered to manage the risk factors for substance abuse in the waste management sector.